Pengembangan Bahan Ajar Cetak dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam - Hafid Muslih; Haerani Wahidah (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
Islamic Religious Education (PAI) plays an important role in education, being the main channel for transferring Islamic values to the younger generation. This study explains the theoretical background regarding the objectives of PAI, including the formation of a true Muslim individual, harmonization with God and the universe, and proper understanding of Islamic teachings. It also highlights the challenges in PAI teaching practices, especially in achieving holistic learning outcomes. The research method focused on analyzing the need for developing printed teaching materials to improve the quality of PAI learning. The analysis includes an understanding of the curriculum, selection of appropriate learning resources, and determination of the type of teaching materials that suit learning needs. The results of this analysis become the basis for developing effective and relevant printed teaching materials. Discussions on the development of PAI print teaching materials emphasize the importance of considering competency standards, appropriate language selection, appropriate teaching methods, and inclusiveness in content delivery. This is aimed at achieving holistic and comprehensive learning objectives in Islamic education. The conclusion of this study reconfirms the importance of developing holistic, interactive, and inclusive printed teaching materials to improve the quality of Islamic Education learning. By considering these aspects, it is expected to achieve sustainable learning objectives and make a positive contribution to learners' understanding and practice of Islamic teachings in daily life.